Effects of sediment disturbance regimes on Spartina seedling establishment: Implications for salt marsh creation and restoration. (18th September 2017) - Cao, Haobing; Zhu, Zhenchang; Balke, Thorsten; Zhang, Liquan; Bouma, Tjeerd J.
Abstract: Seedling establishment is an important process relevant for the restoration of salt marsh within the framework of sustainable coastal defense schemes. Recent studies have increasingly highlighted how the short‐term (i.e., the day‐to‐day) sediment dynamics can form major bottlenecks for seedling establishment. Until recently, studies on quantifying the threshold values of such short‐term sediment dynamics for marsh seedlings remain rare. As accretion/erosion trends and dynamics may differ greatly under global change, we study the effects of short‐term sediment disturbance‐regimes on seedling establishment of two globally distributed foundation species: Spartina alterniflora and Spartina anglica . Seedlings with different disturbance‐free periods were exposed to a set of different accretion/erosion‐regimes in the laboratory. Seedling survival appeared to be much more sensitive to erosion than accretion, seedlings with short disturbance‐free periods were more sensitive than seedlings with longer ones, and S. alterniflora was more sensitive than S. anglica . Seedlings were less sensitive to gradual changes in sediment height (accretion/erosion) than to abrupt changes where time for morphological adjustment is lacking. Critical erosion depth (the maximum erosion that seedlings are able to withstand) was shown to mainly depend on sedimentation history. Our results confirm that the establishment of Spartina seedlings requires a flooding disturbance‐free "window of opportunity" and that sediment disturbances affect their survival both directly and via morphological adjustment. These results provide fundamental insights into seedling establishment that can be used for designing engineering measures to create suitable conditions and enable marsh creation/restoration for nature goals or as part of coastal defense schemes under global change.